2015
DOI: 10.1007/s11010-015-2477-0
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells

Abstract: The emerging role of stress-related signaling in regulating cancer development and progression has been recognized. However, whether stress serves as a mechanism to promote gastric cancer metastasis is not clear. Here, we show that the β2-AR agonist, isoprenaline, upregulates expression levels of CD44 and CD44v8-10 in gastric cancer cells. CD44, a cancer stem cell-related marker, is expressed at high levels in gastric cancer tissues, which strongly correlates with the occurrence of epithelial-mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…It will be important to characterize if β 2 AR agonism induces similar behavior in other tumor cell lines and in vivo . Notably, several recent in vitro studies suggest that βAR signaling induces an epithelial-mesenchymal transition in gastric, colon and lung cancer cell lines (Lu et al, 2015; Shan et al, 2014; Zhang et al, 2016). To better understand βAR regulation of epithelial-mesenchymal transition it will be necessary to clarify the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to characterize if β 2 AR agonism induces similar behavior in other tumor cell lines and in vivo . Notably, several recent in vitro studies suggest that βAR signaling induces an epithelial-mesenchymal transition in gastric, colon and lung cancer cell lines (Lu et al, 2015; Shan et al, 2014; Zhang et al, 2016). To better understand βAR regulation of epithelial-mesenchymal transition it will be necessary to clarify the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have suggested that EMT has a high correlation with the generation of cancer stem cells, the malignancy of tumour cells and the resistance to anticancer therapies (McConkey et al 2009;Zhang et al 2011;Kayastha et al 2015). It has been demonstrated that HMGA2 has an effect on the EMT in many cancer cells, such as colon (Li et al 2014a, b), gastric (Lu et al 2015) and hepatocellular cancer (Li et al 2014a, b). In addition, numerous studies have verified that invasive ability of cancer cells can be regulated by MMPs (Kessenbrock et al 2010), in which MMP-2 and MMP-9 were reported to be closely associated with advanced tumour stage, increased invasion and metastasis, and shortened survival time (Slattery et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…CagA-positive H. pylori infection induces EMT, and CSCs feature in gastric mucosal cells via overexpression of the Wnt/β-catenin signaling pathway [137]. The progression of CSCs is stimulated by EMT-related CD44+ cells' emergence [303][304][305][306][307]. It was hypothesized that overexpression of the regulator of G-protein signaling pathway 1 (RGS1) might promote the transition of stem cells into CSCs [308].…”
Section: Stem Cellsmentioning
confidence: 99%